The Effect of Family Support on the Level of Adherence to Medication Among Pulmonary Tuberculosis Patients at the Tenggarong District Health Center - Apriani, Diana Kurnia; Al-Mubarak, Agustiqori; Pratama, M. Yudha (Jurnal Pijar Mipa, 2025)
Tuberculosis (TB) remains one of the leading causes of death worldwide, and the success of its treatment largely depends on patient adherence to medication. Since non-adherence is still common, this study aims to analyze the influence of family support on medication adherence among pulmonary TB patients at the Tenggarong District Health Center, Indonesia. The research employed a quantitative method with a cross-sectional design and a prospective approach, involving 60 patients with pulmonary TB selected through convenience sampling. The research instruments included a demographic questionnaire, a family support questionnaire, and the Morisky Medication Adherence Scale-8 (MMAS-8) to assess patient adherence levels. The results showed that most respondents received good family support (95%) and had a high level of adherence (86.67%). The chi-square test indicated a significant relationship between family support and medication adherence (p = 0.000), while multivariate analysis using Principal Component Analysis (PCA) also confirmed a positive correlation between the two variables.